NURSES’ COMPLIANCE IN APPLYING INDEPENDENT DOUBLE CHECK IN DRUG ADMINISTRATION - Selvi Kadang; Putri Natalia Sitanggang; Rachel Pratylia Sanjun; Yenni Ferawati Sitanggang; Erivita Sakti (Universitas Pelita Harapan, 2021)
Independent Double Check (IDC) is a strategy that plays a key role in medication safety. Studies have shown that its use can detect up to 95% of medication errors reducing incidents related to drug administration. Despite this benefit, not all nurses have implemented it. This study aims to describe nurses’ compliance in applying IDC at a private hospital in West Indonesia. The study used the descriptive quantitative method and purposive sampling was utilized in choosing 52 respondents. Data were collected from the respondents working in two inpatient wards where the highest number of medication errors occurred. A checklist was used to observe the nurses administer medications to patients in three occasions. The analysis of data employed univariate analysis method. The results showed that 35 (67.3%) of the respondents implemented IDC before medication administration, while 17 (32.7%) did not implement it. However, those who implemented IDC did not contribute to the reduction of medication errors in these wards. The authors recommend that further studies be conducted to investigate the factors associated with nurses’ compliance and non-compliance in applying IDC, and the relationship between nurses’ compliance to IDC and incidents of medication errors.